Interacting and teaching words in natural science classes - Menti, Alejandra; Dutari, María Paula; Carignano, Sebastián (Lenguas Modernas, 2021)
The present study aimed to analyze opportunities that are presented to kindergarten and first grade students to learn spontaneously words in science classes. Qualitative and quantitative analysis procedures were used. The results of this study showed that in science classes teachers observed at kindergarten and first grade of elementary school levels generated similar linguistic and discursive contexts during spontaneous teaching of unknown and unfamiliar words. If vocabulary is a powerful predictor of literacy, analyzing the opportunities that children have to learn words allows us to weigh the quality of teaching situations.